Edgar Allan Poe’s Gothic Revisited in André Øvredal’s The Autopsy of Jane Doe - Lopes, Elisabete (2020)
The Autopsy of Jane Doe (2016), directed by André Øvredal, is a horror film that was widely acclaimed by the critics and audiences alike, due to the originality with which it tackled horror and manipulated both its Gothic features and the supernatural. The plot is quite simple, but its underlying implications are far more complex. Two men, father and son, both coroners, are asked to examine the body of a young woman whose origins are unknown. The corpse, named Jane Doe (because its origins are unknown), is supposedly connected with a crime, since it was found partially unearthed in the cellar of a house whose owners appear to have been brutally murdered. What contributes to render Øvredal´s cinematic narrative interesting, is the mise-en-scène of certain tropes and references that tie in with the American Gothic tradition. Eerie ambiances, psyches on the verge of disintegration, latent family tension, doppelgängers, and the house itself seem to carry echoes of Edgar Allan Poe’s tales, such as “The Fall of the House of Usher”, “Ligeia” or “The Black Cat”. Moreover, we must not forget that at the centre of this visual narrative, lies the inert body of a young woman, recently unburied, an image that is quite recurrent in Poe’s literary works. Within this suggestive framework, the purpose of this paper is to underscore the Gothic influence of Poe’s fiction upon Øvredal’s film, highlighting the relevance of the feminine presence (connoted with a female monster) as a crucial engine that propels the visual narrative forward, eventually turning a medical act, an autopsy, into a horror tale.